2015 IEEE 12th International Conference on Wearable and Implantable Body Sensor Networks (BSN) 2015
DOI: 10.1109/bsn.2015.7299392
|View full text |Cite
|
Sign up to set email alerts
|

Sampling rate impact on energy consumption of biomedical signal processing systems

Abstract: Long battery runtime is one of the most wanted properties of wearable sensor systems. The sampling rate has an high impact on the power consumption. However, defining a sufficient sampling rate, especially for cutting edge mobile sensors is difficult. Often, a high sampling rate, up to four times higher than necessary, is chosen as a precaution. Especially for biomedical sensor applications many contradictory recommendations exist, how to select the appropriate sample rate. They all are motivated from one poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…None of the previous studies evaluated different positions of sensors in terms of accuracy of classification for eating behaviour in sheep and used sampling rate of 20–25 Hz [ 2 ]. Position and sampling rates could impact the accuracy of the algorithms, with higher sampling rate resulting in higher power consumption [ 22 ]. In our previous work we demonstrated that when using an accelerometer and gyroscope sensor the optimum sampling rate needed to classify lying, standing and walking behaviour in sheep with respect to accuracy and energy efficiency is 16 Hz with a 7-s sample window [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…None of the previous studies evaluated different positions of sensors in terms of accuracy of classification for eating behaviour in sheep and used sampling rate of 20–25 Hz [ 2 ]. Position and sampling rates could impact the accuracy of the algorithms, with higher sampling rate resulting in higher power consumption [ 22 ]. In our previous work we demonstrated that when using an accelerometer and gyroscope sensor the optimum sampling rate needed to classify lying, standing and walking behaviour in sheep with respect to accuracy and energy efficiency is 16 Hz with a 7-s sample window [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several detailed studies are presented by Tobola et al in which they compare different microcontrollers for WSNs [4], quantify the impact of different sampling rates for various algorithms [5], and optimize the hard-and software implementation of an ECG sensor [6]. Likewise, Berlin et al [7] increased the runtime of a wearable data logger by varying the sampling rates, the low-power modes, the type of used SD-card and by applying a run length encoding.…”
Section: Related Workmentioning
confidence: 99%
“…If we consider this new scenario, the portable devices strongly constraint the maximum power consumption of the system. In order to enlarge the battery life-time, one possible approach is the reduction of the sampling rate of the sensing node [2], leading to a reduction of data density and signal bandwidth. In fact, the key components of the power consumption in the device are related to the power spent by signal elaboration and data transmission, which are both directly influenced by the sampling rate.…”
Section: Introductionmentioning
confidence: 99%